Assessing the development of performance audit methodology in the supreme audit institution: The case of Indonesia - Andrianto, Nico; Sudjali, Iwan Purwanto; Karunia, R. Luki (Jurnal Tata Kelola dan Akuntabilitas Keuangan Negara, 2021)
Badan Pemeriksa Keuangan (BPK), or The Audit Board of the Republic of Indonesia, has introduced performance audits intensively since public sector audit reforms were initiated in 2001. However, the implementation of performance audits still faces several obstacles. This study examines the development of the performance audit methodology in BPK, which can be divided into three stages: before the revitalization of BPK in 2006, the initial development of performance audits during 2006-2010, and the maturity of the implementation of performance audits since 2011. This study concludes that several key factors have affected the implementation of performance audits at BPK, including the development of audit guidelines, the dynamics of medium-term government planning, the focus of the BPK’s Management, and assistance provided by other supreme audit institutions (SAI). To address new realities and challenges in the future, more sophisticated performance audit methods need to be adopted by BPK, such as big data analytics, the adoption of governance audits, and employing public policy analysis. Without adopting such methods, the institutionalization of ​​effective performance audits might not be achieved in the future.